University innovation and start‐ups: Barriers and facilitators experienced by nursing faculties - A content analysis study - Zahra Jamshidi; Mojtaba Aieen; Mehdi Jafari‐Oori (Wiley, 2024)
Abstract Aim University start‐ups have gained significant popularity as a means of translating knowledge and research into practical applications. However, there is a lack of understanding regarding the experiences and perspectives of nursing faculties engaged in start‐up ventures. The objective of this study was to explore valuable insights into the barriers and facilitators within this context for promoting success, generating entrepreneurial attitudes, as well as enhancing the sustainability of nursing faculty‐led start‐ups. Design We employed a content analysis methodology to capture the real‐life experiences of nursing faculties involved in university start‐ups. This approach is an effective way to gain a comprehensive understanding of the subject. Methods Data were collected using semi‐structured interviews. Graneheim and Lundman's step was used for analysis and to identify recurring patterns and themes within the collected data. Sampling was done purposefully, with convenience and snowball techniques until data saturation. The MAXQDA version 10 software was utilised to easily analyse, code and present data. Results The analysis revealed four major themes encompassed: motivational factors, personal attributes, limited entry support and barriers to scaling. These themes shed light on factors, support systems, challenges faced during growth as well as personal characteristics highlighted by the participants. Our study highlighted the factors influencing entrepreneurship in nursing faculties. Addressing the challenges of this study requires enhancing support systems and fostering personal development for entrepreneurial success in healthcare innovation. Policymakers can promote university education to expand the entrepreneurship process using more facilities and make more services accessible.